Edukasi Kesehatan Mental dan Pemeriksaan DASS-42 untuk Pencegahan Burnout dan Gangguan Afektif pada Usia Produktif - Anastasia Ratnawati Biromo; Alexander Halim Santoso; Edwin Destra; Kresna Bambang Fajarivaldi; Disya Gwyneth` Aziel (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Mental health in productive-age individuals is an important aspect to consider, given that this age group has a high potential for experiencing emotional stress due to work, social, and personal demands. Unfortunately, psychological disorders such as depression, anxiety, and stress are often not recognized early because their symptoms are subclinical or hidden. Based on this background, mental health screening and education activities were conducted to support promotive and preventive efforts in maintaining the psychological well-being of productive-age individuals. Screening was conducted using the 42-item version of the Depression Anxiety Stress Scales (DASS-42) instrument on 49 participants within the productive age range. After completing the questionnaire, participants received a collective education session delivered through posters. The educational material was tailored to the measurement results and distribution of DASS-42 scores obtained from the participants. The aim of this approach was to raise awareness of each individual's psychological condition and equip participants with knowledge about the early symptoms of common mental disorders. The screening results showed that a proportion of participants experienced mild to severe psychological symptoms, particularly in the anxiety domain. This finding indicates a hidden emotional burden that is not yet recognized by the individuals concerned. Through the delivery of visual education based on population measurement results, participants gained a better understanding of the urgency of early recognition of psychological problems and the importance of maintaining ongoing mental health. This activity demonstrated that visual education, such as posters, can be an effective tool in increasing mental health literacy among those of working age. Furthermore, the data-driven approach provided a more relevant and personalized impact, thus encouraging participant engagement in mental health prevention efforts.